Blurred Lines: Migration and Mobility in EU Law and Policy - Bauloz, Céline (My University, 2016)
While the movement of persons is at the heart of the European construction, it has been conceptualised differently with regard to third-country nationals and citizens of the European Union (EU). In the former case, it is referred to as ‘migration’ and, in the latter, as ‘mobility’. This traditional perception of migration and mobility is however not set in stone but is deemed to evolve alongside the ever-changing migratory reality and interests of the different stakeholders. The present paper examines these traditional conceptions and their development in European law and policy drawing from EU policy documentation as well as both primary and secondary law. It highlights a shift in the migration-mobility discourse from a migration-mobility dichotomy to a migration-mobility nexus where migration is increasingly treated qua mobility. The paper further explores the limits of this analogy and its potential for a more comprehensive rethinking of migration at the EU level.
Keywords: migration; mobility; European Union law and policy; movement of persons; free movement; third-country nationals